PN TOMOGRAPHIC IMAGING OF MANTLE LID VELOCITY AND ANISOTROPY AT THE JUNCTION OF THE ARABIAN, EURASIAN AND AFRICAN PLATES - Al-Lazki A.I.; Seber D.; Barazangi M.; Sandvol E.; Turkelli N.; Mohamad R. (My University, 2004)
The interaction of the Arabian plate with the Eurasian plate has played a major role in building the young mountain belts along the Zagros–Bitlis continent–continent collision zone. Arabia's northward motion is considered to be the primary driving force behind the present-day westerly escape of the Anatolian plate along the North and East Anatolian fault zones as well as the formation of the Turkish and the Iranian plateaux. In this study we mapped Pn-wave velocity and anisotropy structures at the junction of the Arabian, Eurasian and African plates in order to elucidate the upper-mantle dynamics in this region. Pn is a wave that propagates within the mantle lid of the lithosphere and is often used to infer the rheology and fabric of the mantle lithosphere. Applying strict selection criteria, we used arrival times of 166 000 Pn phases to invert for velocity and anisotropy in the region. Using a least-squares tomographic code, these data were analysed to solve simultaneously for both velocity and azimuthal anisotropy in the mantle lithosphere. We found that most of the continental regions in our study area are underlain by low Pn velocity structures. Broad-scale (∼500 km) zones of low (<8 km s−1) Pn velocity anomalies underlie the Anatolian plate, the Anatolian plateau, the Caucasus region, northwestern Iran and northwestern Arabia, and smaller scale (∼200 km), very low (<7.8 km s−1) Pn velocity zones underlie southern Syria, the Lesser Caucasus, the Isparta Angle, central Turkey and the northern Aegean Sea. The broad-scale low-velocity regions are interpreted to be hot and unstable mantle lid zones, whereas very low Pn velocity zones are interpreted to be regions of no mantle lid. The low and very low Pn velocity zones in eastern Turkey, northwestern Iran and the Caucasus region may be associated with the latest stage of intense volcanism that has been active since the Late Miocene. The low Pn velocity zones beneath the Anatolian plate, eastern Turkey and northwestern Iran may in part be a result of the subducted Tethyan oceanic lithosphere beneath Eurasia. We also found a major low-velocity zone beneath northwestern Arabia and the Dead Sea fault system. We interpret this anomaly to be a possible extension of the hot and anomalous upper mantle of the Red Sea and East Africa rift system. High Pn velocities (8.1–8.4 km s−1) are observed to underlie the Mediterranean Sea, the Black Sea, the Caspian Sea, and the central and eastern Arabian plate. Observed Pn anisotropy showed a higher degree of lateral variation than did the Pn velocity structure. Although the Pn anisotropy varies even in a given tectonic region, in eastern Anatolia very low Pn velocity and Pn anisotropy structures appear to be coherent.
Keywords: anisotropy; Arabia; Middle East; Pn; tomography; velocity